Gambaran Pelaksanaan Program Pelayanan Voluntary Counseling and Testing (Vct) di Rumah Sakit Kota Sorong - Maria Karolina Selano (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2018)
Background : HIV Counseling and Testing is a key component in HIV programs in both developed and developing countries, including Indonesia. VCT clinic is the gateway for obtaining information on HIV / AIDS. Acquired Immuno Deficiency Syndrome (AIDS) is a collection of symptoms of diseases caused by the decline in the human immune system caused by the HIV virus that has attacked almost all countries in the world, including Indonesia. This research aims to know the description of VCT service program implementation in Sorong City Hospital in 2018. Methods : This research type is qualitative research with descriptive approach. Informants obtained from purposive sampling of 7 informants. Result : The results of this study indicate that the inputs have been good, that is the number of trained human resources with the educational background in accordance with this program, the tools that support the implementation of the program and the funds for the program are available and sufficient. Conclusion : Description of the process of VCT service program implementation in view of the number of patients receiving VCT services is good because there is a referral system between all service units in both inpatient and outpatient services.